Exploring the Implementation of a Blended Learning Approach in Teaching an English Writing Course at a Bangladeshi University - Md Khaled Bin Chowdhury
Against the backdrop of problems in Bangladeshi higher education like seat crises and session backlogs in public universities, high tuition fees in private universities, a lack of student loans, and the negative perception of online education among people including policymakers, teachers, parents, and students, it is assumed that blended learning can be an effective mode of education for Bangladesh’s universities for a number of reasons such as flexibility, enhanced learning outcomes, more teacher-student interaction, and more student satisfaction in general. So, this study was conducted to investigate the perceptions of students and teachers about both online and face-to-face education and their experiences with blended learning. The research questions of this study centered around issues like whether blended learning is appropriate as an alternative mode of education in the 21st century, what were the experiences of teachers and students with using blended learning in an English Writing Course at the undergraduate level and whether blended learning could solve the problem of space, session backlog in the public universities, reduce the cost of higher education and other problems of higher education institutions of Bangladesh. This is a qualitative, in particular, case study. The data came from interviews with 15 student participants doing the course and two teachers who conducted the course, their discussions, and postings on online forums, such as Facebook, Google Classroom, a Blog, student journals, and essay scores of 15 students. Data collected from these sources were analyzed following the qualitative data analysis method. The participants mentioned a number of advantages and disadvantages of both face-to-face and online education in Bangladesh. Most of the participants in this study opine that against the backdrop of the problems and challenges of both online and face-toface education, the blended method can be an effective alternative mode of education for the universities of Bangladesh. This method, they reported, offered them opportunities such as more flexibility, increased learning through teacher and peer feedback, scope for self-exploration, better and enhanced interaction, reduction in tuition fees and other costs of education, easing of traffic jam, expansion of women education, an increase of technological skills, and higher-order thinking. On the other hand, they mention a number of challenges of blended method such as the digital divide, the lack of teacher training and infrastructural barriers. This study can guide the policymakers, institution managers, teachers and students in Bangladeshi higher education for the implementation of the blended learning method as a way to improve the quality of higher education even in the face of infrastructural and resource constraints in the universities.